PENGARUH FINANCIAL ATTITUDE DAN FINANCIAL KNOWLEDGE TERHADAP PERSONAL FINANCIAL MANAGEMENT MAHASISWA UNIVERSITAS INTERNASIONAL BATAM - Yulfiswandi Yulfiswandi; Ellen Ellen; Florentina Jasmine; Lovis Vernando; Kelvin Kelvin; Vincent Vincent (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
Each individual has their own assets, but the important thing is how to manage them properly and correctly. A bad investment or even consumptive behavior will cause the person to experience losses and bankruptcy. Lack of knowledge and education about managing finances will be a big challenge, especially for students. This research aims to examine the effect of financial knowledge and financial attitude on the personal financial management of Batam International University students. Data was obtained by filling out questionnaires, which were distributed to 97 students at Batam International University using Google Forms as a data collection tool. The analytical method used in this study is the partial least squares structural equation model (PLS-SEM). Based on the results of the research, it can be concluded that financial knowledge and financial attitude have a significant positive effect on financial management.